San Francisco Museum of Modern Art : Annual Report 1999-2000. - McKeon, Elaine; Ross, David A.; SFMOMA (San Francisco Museum of Modern Art) San Francisco (San Francisco : SFMOMA (San Francisco Museum of Modern Art), 2001)
Abbott, Berenice ; Barney, Matthew ; Burden, Chris ; Evans, Frederick H. ; Evans, Walker ; Fried, Howard ; Gedney, William ; Gehry, Frank O. ; Hatoum, Mona ; Hesse, Eva ; Irving, James ; Johns, Jasper ; Jongerius, Hella ; Kalpakjian, Craig ; Klutsis, Gustav Gustavovich ; LeWitt, Sol ; Lutter, Vera ; Maeda, John ; Magritte, René ; Marclay, Christian ; Marey, Etienne-Jules ; Marshall, Kerry James ; Nelson, George ; Ofili, Chris ; Simon, John ; Thiebaud, Wayne ; Twombly, Cy ; Walker, Kara
Engels
boek